A bibliography relative to teaching and learning English as a second language - Cabrera, Patricia; California State Dept. of Education, Sacramento. Bureau of Adult Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1967)
Materials in this annotated bibliography have publication dates 1954-66, and were collected for a (California) statewide plan for the development and implementation of curricula research programs involving adult students with Spanish surnames, funded in May 1965 under title v of the elementary and secondary education act. Materials of interest to teachers of English as a second language are divided into groups--application, linguistics, language and related disciplines, periodicals, and textbooks and materials. Sources for the bibliography are given. (aj)
Microfiche.
Keywords: Annotated Bibliographies; English (Second Language); Instructional Materials; Language Instruction; Linguistics; Periodicals; Reading Materials; Second Language Learning; Spanish Speaking; Teaching Methods; Textbooks